Building ecosystem resilience for climate change adaptation in the Asian highlands - Xu, J.C.; Grumbine, R. Edward (Wiley, 2014)
The Asian Highlands, the vast mountainous area from Pakistan to China including the Hindu‐Kush Himalaya and Tibetan Plateau, have considerable global importance; they are the source of most of the major rivers of Asia, which sustain billions of downstream dwellers, are part of four Global Biodiversity Hotspots, and support rich cultural diversity. However, climate warming in the Himalaya–Tibetan Plateau has been greater than two times the global average, and regional climate appears to be shifting with potential to trigger large‐scale ecosystem regime shifts (‘landscape traps’). A host of other drivers—urbanization/infrastructure development, land‐use/agricultural practices, upstream/downstream water management and ongoing nation‐state security conflicts—interact with climate signals to produce complex changes across ecological and social systems. In response, highlands people are evolving hybrid forms of adaptive capacity where ‘bottom‐up’ behaviors are mixing with ‘top‐down’ state and market policies. To increase ecosystem and livelihood resilience to future change, there is a need to link upstream and downstream conservation action with local climate adaptation. While the key problem is that institutional and government capacity for coordination is low, we present four general strategies to move forward: application of cross‐sector coordinated planning, strategic integration of science‐based conservation with developing local‐level hybrid knowledge, recognition of the critical role of governance in support of change, and increased emphasis on environmental security. We discuss these strategies for each driver of change in the region. WIREs Clim Change 2014, 5:709–718. doi: 10.1002/wcc.302